Character Development in the Independent Curriculum through the Application of Serviam Values at SD Yuwati Bhakti Sukabumi - Nurkristianti, Agnes Aprillia; Saryanto, Saryanto (Asosiasi Ide Bahasa Kepri, 2025)
This study aims to determine character development through the application of service values at SD Yuwati Bhakti Sukabumi. The research method used the interview method. Serviam values are the basis for the implementation of education at SD Yuwati Bhakti Sukabumi. The basic values of serviam are the implementation of OSU's basic values. The basic values of serviam are the basis for character development at SD Yuwati Bhakti Sukabumi in the independent curriculum. The application of serviam values through daily habituation in learning the independent curriculum helps to form a positive character of students. The results of the study show that the Independent Curriculum is implemented by providing a large space for differentiated learning, a project to strengthen the Pancasila student profile (P5), and an emphasis on learning based on noble values. Educators at SD Yuwati Bhakti integrate Serviam values into learning activities and P5 projects consistently.